Projek perintis program rawatan terapi gantian (RTG) menggunakan methadone di Pusat Khidmat AADK - Kaur, Sangeeth; Mohd, Hafidah; Mohamed, Mahmood Nazar (Agensi Antidadah Kebangsaan, 2009)
The National Anti-Drugs Agency has played a pivotal role in implementing a Pilot Project of the Methadone Maintenance Therapy at three AADK After Care Centers in Malaysia since 26 November 2007. Evaluation of this program has shown encouraging success by achieving a retention rate of 92.9% in the first 12 months. The result of the evaluation also has proven to reduce the number of 'slip' (infrequent drug use) cases while undergoing this program. The program has also helped clients in gaining employment thus reducing crime rate. At the same time the Methadone Maintenance Therapy Program has improved the quality of life of these clients especially in the aspect of physical, social and environment. This Program aims to provide hope for these clients to achieve a better quality of life and be able to contribute as productive individuals to the nation.